Necrotizing fasciitis caused by Apophysomyces variabilis in a burn patient. (2019) - Samaddar, Arghadip; Sharma, Anuradha; Maurya, Vinod Kumar; Tak, Vibhor
Abstract: The genus Apophysomyces belonging to the order Mucorales is increasingly being reported as a cause of mucormycosis in immunocompetent patients. We report a case of necrotizing fasciitis caused by Apophysomyces variabilis in a 52-year-old immunocompetent male who sustained thermal burn in his right leg following a road-traffic accident. There was rapidly progressive necrosis of skin, soft tissues and underlying muscles which required extensive surgical debridement. Microscopic examination of excised tissues revealed broad aseptate fungal hyphae. Fungal culture on Sabouraud dextrose agar (SDA) showed growth of a mucoraceous mould which was identified as A. variabilis based on characteristic microscopic morphology and internal transcribed spacer sequencing of the ribosomal DNA. The isolate was found to sporulate on SDA, a finding that was unique as Apophysomyces spp. does not usually sporulate on primary isolation medium used in mycology laboratories. The disease progressed as there was an initial assumption of bacterial infection and the fungus was isolated late in the course of the disease because of which no antifungal drug was added to the regime. The patient left against medical advice and eventually underwent below-knee amputation at another city hospital a week later. Infection due to A. variabilis should be considered as a differential diagnosis of rapidly progressive necrosis of skin and soft tissues in immunocompetent individuals as early diagnosis and management will prevent the disease progression and a possible amputation.